Economic theories, true or false: essays in the history and methodology of economics - Blang, Mark (Aldershot, 1990)
Mark Blaug has achieved an international reputation primarily through his seminal contributions to economic methodology and the history of economic thought. This important new book presents in one volume some of his most important recent essays on economic theory. A lucid evaluation of Marxian economics is followed by an assessment of radical economics, Keynesian economics and the economic ideas of the late Sir John Hicks. In addition, there are a number of essays on the history of economic thought including studies of Von Thünen. Nicholas Kaldor and Pierro Sraffa. In conclusion, there are es says on the alternative interpretation of classical economics as well as an appraisal of the influence of neo-Ricardian economics on modern economic theory.
Keywords: Economics